1995
DOI: 10.1254/jjp.69.215
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effect of Chronic KT3-671, a Structurally New Nonpeptide Angiotensin AT1-Receptor Antagonist, in Stroke-Prone Spontaneously Hypertensive Rats

Abstract: ABSTRACT-KT3-671(2-propyl-8-oxo-1-[(2'-(1H-tetrazole-5-yl)biphenyl-4-yl)methyl]-4,5,6,7-tetrahydrocycloheptimidazole), a structurally new nonpeptide angiotensin AT,-receptor antagonist, was administered orally and repeatedly to 15-week-old stroke-prone spontaneously hypertensive rats for 7 weeks; and its effects on blood pressure, heart rate, renal function, plasma renin concentration (PRC), plasma aldosterone concentration (PAC) and hypertension-related tissue damage in the brain, heart, kidney and mesenteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This difference may result from the dose of enalapril used and/ or severity of glomerular alterations. Amano et al demonstrated that repeated administration of KD3-671 (10 mg/kg) to 15-week-old stroke-prone spontaneously hypertensive rats for 7 weeks did not affect renal function during the experimental period (12). In this study, KD3-671 (30 mg/ kg per day) had no effect on urea nitrogen, which was measured for evaluating renal function.…”
mentioning
confidence: 45%
“…This difference may result from the dose of enalapril used and/ or severity of glomerular alterations. Amano et al demonstrated that repeated administration of KD3-671 (10 mg/kg) to 15-week-old stroke-prone spontaneously hypertensive rats for 7 weeks did not affect renal function during the experimental period (12). In this study, KD3-671 (30 mg/ kg per day) had no effect on urea nitrogen, which was measured for evaluating renal function.…”
mentioning
confidence: 45%
“…KT3-671 produces sustained decrease in blood pressure and attenuates ang IIinduced pressor response after oral administration to rats (Yanagisawa et al, 1993) and dogs (Takata et al, 1998). KT3-671 does not affect normal renal function and reduces hypertension-induced pathological changes in the kidney (Amano et al, 1995). KT3-671 has recently been demonstrated to produce vascular sympathoinhibitory activity (Takata et al, 2001).…”
Section: Nonpeptide At 1 Receptor Antagonists Under Clinical Trialsmentioning
confidence: 99%
“…KT3-671 is a novel chemical entity, which has been shown to be a potent, orally active, specific AT 1 receptor antagonist. KT3-671 has undergone in vitro and in vivo pharmacological studies in which it demonstrated a selective affinity for AT 1 receptors in a variety of animal models where a dose dependent reduction in blood pressure (BP) was observed [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%